1996
DOI: 10.1002/eji.1830261244
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Apo‐1/Fas (CD95)‐induced programmed cell death in myeloma cells by interferon‐α2

Abstract: The Apo-1/Fas (CD95) antigen is known to be involved in the process of T cell-mediated target cell killing and has recently been shown to be expressed on myeloma cell lines and native malignant plasma cells. Several cytokines have been reported to interfere with spontaneous and even Apo-1/Fas-induced apoptosis, but no attempt has been made yet to investigate these interactions and the possible underlying mechanisms in myeloma cells. Since in myeloma patients Interferon (IFN)-alpha2 displays a profound therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 42 publications
3
23
0
Order By: Relevance
“…In contrast to the uptake of apoptotic cells by DCs, which results in the processing and presentation of Ag to T cells (1), the CD14-mediated uptake of apoptotic cells by macrophages diverts the phagocytosed antigenic material from T-cell recognition (17). This mechanism could be enhanced by the known effect of IFN-␣ on the CD95-mediated pathway of apoptosis: increased levels of expression of CD95 on infected cells (12,28,45) and the concomitant up-regulation of the Fas ligand on NK effector cells (20) may result in the accelerated apoptosis of infected cells, which in turn are removed by CD14-expressing Kupffer cells without further activation of the infiltrating lymphocytes. In line with this interpretation, we found no evidence of a significant involvement of DCs in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the uptake of apoptotic cells by DCs, which results in the processing and presentation of Ag to T cells (1), the CD14-mediated uptake of apoptotic cells by macrophages diverts the phagocytosed antigenic material from T-cell recognition (17). This mechanism could be enhanced by the known effect of IFN-␣ on the CD95-mediated pathway of apoptosis: increased levels of expression of CD95 on infected cells (12,28,45) and the concomitant up-regulation of the Fas ligand on NK effector cells (20) may result in the accelerated apoptosis of infected cells, which in turn are removed by CD14-expressing Kupffer cells without further activation of the infiltrating lymphocytes. In line with this interpretation, we found no evidence of a significant involvement of DCs in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies examining the killing of other cell types by IFN have implicated CD95/CD95L. 22,24,28,30,42 We therefore examined the role of these proteins in the IFN-␣-induced killing of HCs. Our demonstration that CD95/CD95L is not involved suggests that HCs may belong to the category of type II cells, which express CD95 but fail to form the death-inducing signaling complex.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, Milner et al 8 also demonstrated that IFN-␣ can protect Burkitt's lymphoma lines from Ca 2+ ionophore ionomycin induced apoptosis. In a recent study Egle et al 36 reported that IFN-␣ can block Fasinduced apoptosis in autonomously growing lymphoblastoid…”
Section: Figurementioning
confidence: 99%